Software Quality & Quality Assurance Engineering - Mitchel, Angelique, author 639717; Galvin, Lane, author 643716 (Delhi, India : Academic Studio, 2012)
This book is a complete package for knowledge sharing on Software Quality & Quality Assurance Engineering.